Association Between Changes in Muscle Strength and Risk of Depressive Symptoms Among Chinese Female College Students: A Prospective Cohort Study - Cao, Jianhua; Zhao, Fang; Ren, Zhongyu (Frontiers in Public Health, 2021)
Abstract: Increased physical activity is related to a lower risk of depressive symptoms, and there are prospective associations between baseline muscle strength and the incidence risk of depressive symptoms among the elderly. This study aimed to examine the prospective association between change of handgrip strength, a representative indicator of skeletal muscle strength, and the incidence risk of depressive symptoms among Chinese female college freshmen. A one-year prospective (n = 599) study were conducted to examine the association between handgrip strength and risk of depressive symptoms. Handgrip strength was measured with a handheld digital smedley dynamometer. Depressive symptoms were evaluated using the 20-item Zung self-rating depression scale (a score of ≥50 indicated moderate-to-severe depressive symptoms). During a one-year follow-up period, 10.7% of participants were classified as having moderate-to-severe depressive symptoms. Multivariate logistic regressions analysis revealed that the multivariable-adjusted ORs (95% CI) of depressive symptoms across the quintiles of for change in handgrip strength was 1.00 (reference) for quintile 1, 0.897 (0.440, 1.828) for quintile 2, 0.455 (0.202, 1.021) for quintile 3 and 0.459 (0.201, 1.049) for quintile 4 (p = 0.024). Our findings indicate that increasing handgrip strength may lower the risk of depressive symptoms among Chinese female college freshmen. Further interventional studies are needed to explore the mechanisms underlying the effects of handgrip strength on depressive symptoms.